Penerapan Metode EOQ Dalam Pengendalian Persediaan Bahan Baku Di CV Javatech - Fadilah Muhamad; Puji Isyanto (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This research discusses the application of the Economic Order Quantity (EOQ) method to controlling raw material inventory at CV Javatech. The aim of this research is to investigate the effectiveness of the EOQ method in improving raw material inventory management and its impact on the company's operational performance. The research method used is quantitative with a focus on the use of the EOQ model in determining the economic amount of raw materials. The data used includes raw material purchases, raw material usage, storage costs, ordering costs, etc. Data was collected through interviews with warehouse PICs and direct observation of the raw material inventory control process. The research results show that the application of the EOQ method can help CV Javatech in optimizing the raw material procurement process. The EOQ formula is used to determine the cost-effective amount of raw material purchases based on data analysis. Raw material purchases are made nine times a year using the EOQ model. Apart from that, this research also calculates the Total Inventory Cost (TIC) resulting from implementing the EOQ Method which is more efficient compared to inventory control carried out by the CV Javatech company.